2023
DOI: 10.1615/jwomenminorscieneng.v29.i3.30
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Sense of Community, Science Self-Efficacy, and Science Identity for Female Meyerhoff Scholars: Implications for Pathways to Broadening the Workforce in Stem

Abstract: Women remain underrepresented in Science, Technology, Engineering, and Mathematics (STEM) fields, even with the plethora of programs to increase diversity. Understanding the undergraduate experience for female students of color majoring in STEM is critical for determining effective strategies for retention and smooth career pathways. Using data from 96 (predominantly) African-American female and Latina students in the Meyerhoff Scholars Program at the University of Maryland, Baltimore County, this study quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Additionally, the study of local communities in the context of globalization has shown that forming a person's commitment to the place of residence can be achieved through accumulative effect of horizontal connections and network principles of interaction between residents [37]. However, it is important to note that globalization can also have negative impacts on national culture and the fading of national identity [38], [39]. Overall, the relationship between globalization and community identity is complex, with both positive and negative aspects to consider.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the study of local communities in the context of globalization has shown that forming a person's commitment to the place of residence can be achieved through accumulative effect of horizontal connections and network principles of interaction between residents [37]. However, it is important to note that globalization can also have negative impacts on national culture and the fading of national identity [38], [39]. Overall, the relationship between globalization and community identity is complex, with both positive and negative aspects to consider.…”
Section: Discussionmentioning
confidence: 99%